1982
DOI: 10.3109/08820138209057747
|View full text |Cite
|
Sign up to set email alerts
|

Further Aspects of T Cell Function in Systemic Lupus Erythematosus

Abstract: Generation of effector cells, the expression of cell mediated lympholysis (CML) and the reactivity of mononuclear cells in solid cultures, were explored in patients with Systemic Lupus Erythematosus (SLE). While proliferative responses to alloantigens were comparable to the controls, a significant decrease in CML capacity was found in SLE T lymphocytes; further, T cells stimulated with a T cell mitogen in solid cultures showed a diminished proliferative response to soluble factors. Functional cell interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Because our cohort of patients with SLE had predominantly quiescent disease, this may explain their normal responses to SEB. In addition, previous studies showed decreased proliferation of PBMCs (27)(28)(29), whereas others showed a normal proliferative capacity (30) or heterogeneous results (31).…”
Section: Discussionmentioning
confidence: 93%
“…Because our cohort of patients with SLE had predominantly quiescent disease, this may explain their normal responses to SEB. In addition, previous studies showed decreased proliferation of PBMCs (27)(28)(29), whereas others showed a normal proliferative capacity (30) or heterogeneous results (31).…”
Section: Discussionmentioning
confidence: 93%